Development of active rosmarinic acid-gelatin biodegradable films with antioxidant and long-term antibacterial activities. (October 2018) - Ge, Liming; Zhu, Mingjin; Li, Xinying; Xu, Yongbin; Ma, Xiaonan; Shi, Rong; Li, Defu; Mu, Changdao
Abstract: It is significant to develop new approaches to incorporate naturally active agents into gelatin-based edible films for effective antioxidant and long-term antibacterial activities. Here the naturally active compound rosmarinic acid (RosA) was firstly conjugated onto gelatin backbone via EDC/NHS chemistry. Then the conjugates were plasticized by glycerol and crosslinked by dialdehyde xanthan gum to fabricate active RosA-gelatin edible films. The results indicate that the RosA-gelatin edible films present good water resistance property, strong mechanical property and excellent ultraviolet light barrier ability. The conjugation of RosA confers gelatin-based edible films with effective antioxidant and antibacterial activities as expected. It is interesting that RosA-gelatin edible films after 3 months of storage still show good antibacterial activity as that of newly prepared ones, demonstrating the long-term antibacterial activity. Overall, the fabricated RosA-gelatin edible films may have promising application in the fields of food and pharmaceutical packaging. Graphical abstract: Image 1 Highlights: Rosmarinic acid was successfully conjugated onto gelatin via EDC/NHS chemistry. Rosmarinic acid-gelatin was used to prepare active edible film. Rosmarinic acid-gelatin edible film possessed excellent ultraviolet barrier capacity. Conjugated rosmarinic acid provided gelatin with effective antioxidant activity. Rosmarinic acid-gelatin edible film showed long-term antibacterial activity.